Radio frequency system architecture and design - Rogers, John; Plett, Calvin; Marsland, Ian (Artech House microwave library, 2013)
Communication devices such as smart phones, GPS systems, and Bluetooth, are now part of our daily lives more than ever before. This resource describes practical aspects of radio frequency communications systems design, bridging the gap between system-level design considerations and circuit-level design specifications.